Marine Energy Exploitation in the Mediterranean Region: Steps Forward and Challenges - Pisacane, Giovanna; Sannino, Gianmaria; Carillo, Adriana; Struglia, Maria Vittoria; Bastianoni, Simone (Frontiers in Energy Research, 2018)
Technologies for the conversion of Marine Energy (ME) into electricity are now ready for full-scale deployment in farms of devices, making the final step from demonstration to operability and commercial exploitation. Although marine energy is more abundant along the Atlantic and Nordic European coasts, significant resources are also available in the Mediterranean Sea, opening up new perspectives for sustainable energy production in sensitive coastal areas and for the economic development of Southern Europe. The implementation of ME converters in the Mediterranean is also liable to induce significant technological advancements, as the low energy levels impose more restrictive constraints on device efficiency and environmental compatibility, while the milder climate allows the testing of concepts and prototypes in the natural environment at more affordable costs. Research institutions and industrial players in Mediterranean countries have in fact already taken up the challenge. The energy sector now adds up to the many different traditional maritime activities and to the new ocean-related industries that are developing, potentially exacerbating the competition for the use of marine space in the Mediterranean region. As the prospective sea use patterns are rapidly changing, an adequate international legal and policy framework needs to be designed for the coherent management of sea space, and Marine Spatial Planning needs to be finally implemented. To this end, the creation of transnational clusters of stakeholders is expected to be an effective catalyzer.